2020
DOI: 10.15390/eb.2020.8828
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effect of Intervention and Intervention Packages on the Reading Fluency and Comprehension of Lower Secondary School Students with Mental Retardation

Abstract: Bu araştırmada beceri ve performansa dayalı müdahalelerin ve müdahale paketlerinin zihinsel yetersizlikten etkilenmiş öğrencilerin akıcı okumaları ile okuduğunu anlamalarını ne ölçüde etkilediğini belirleme ve Kısa Deneysel Analiz (KDA) sonuçlarını, Genişletilmiş Analiz (GA) ile test etme amaçlanmıştır. Araştırmada, zihinsel yetersizliği olan üç öğrencinin dakikada okuduğu doğru sözcük sayıları ve okuduğunu anlama düzeyleri beş farklı müdahale ve/veya müdahale paketi kullanılarak belirlenmiştir. Araştırma bulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Analysis of the studies based on the educational and grade levels attended by the students revealed that seven studies were conducted with primary school students (2nd, 3rd, and 4th grades) (Cora-İnce, 2007;Dağlı-Gökbulut, 2019;Gevrek, 2018;Işıkdoğan, 2009;Özak, 2017;Vural, 2019;. Nine studies involved at the secondary school level (5th, 6th, 7th, and 8th grades; Çetinkaya, 2018;Çetrez-İşcan & Coşkun, 2016;Çınar, 2019;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Kalkan, 2019;Kavan, 2020;Orçan, & Özmen, 2012;Sanır et al, 2020), two studies focused on high school students (Coşgun-Başar, 2019;Özaydın, 2019), and five studies included students from mixed grade levels (Akoğlu & Turan, 2012;Arslan-Soyaltın et al, 2021;Cüre, 2018;Çetrez-Arıcan et al, 2017;Güldenoğlu & Kargın, 2012). Additionally, three studies (Atik-Çatak & Tekinarslan, 2008;Duman & Çifçi-Tekinarslan, 2007;Kayahan, 2011) focused on primary school students aged between 11 and 15.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the studies based on the educational and grade levels attended by the students revealed that seven studies were conducted with primary school students (2nd, 3rd, and 4th grades) (Cora-İnce, 2007;Dağlı-Gökbulut, 2019;Gevrek, 2018;Işıkdoğan, 2009;Özak, 2017;Vural, 2019;. Nine studies involved at the secondary school level (5th, 6th, 7th, and 8th grades; Çetinkaya, 2018;Çetrez-İşcan & Coşkun, 2016;Çınar, 2019;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Kalkan, 2019;Kavan, 2020;Orçan, & Özmen, 2012;Sanır et al, 2020), two studies focused on high school students (Coşgun-Başar, 2019;Özaydın, 2019), and five studies included students from mixed grade levels (Akoğlu & Turan, 2012;Arslan-Soyaltın et al, 2021;Cüre, 2018;Çetrez-Arıcan et al, 2017;Güldenoğlu & Kargın, 2012). Additionally, three studies (Atik-Çatak & Tekinarslan, 2008;Duman & Çifçi-Tekinarslan, 2007;Kayahan, 2011) focused on primary school students aged between 11 and 15.…”
Section: Resultsmentioning
confidence: 99%